Profitability and Financing Analysis at Sharia Bank in Indonesia - Abral, Edi (International Journal of Economics (IJEC), 2023)
This research aims to determine the influence of Capital Adequacy, Financing Problems and Asset Quality on the Profitability of Sharia Banks in Indonesia. To determine the number of samples, a purposive sampling technique was used. The data used is secondary data, panels in quarters. Data was obtained from the Financial Services Authority/OJK for the period March 2018 to December 2020. Panel Data Regression analysis techniques with Fixed Effect Models were used to analyze the influence of independent variables on the dependent variable. The results of this research indicate that Capital Adequacy, Problem Financing and Asset Quality simultaneously have a significant effect on profitability. Meanwhile, partial testing shows that the Capital Adequacy and Asset Quality variables do not have a significant effect on profitability. The problematic financing variable has a significant negative effect on profitability. This requires efforts to reduce problematic financing so that efforts to increase the profitability of Islamic banks can be carried out in the future